New insights into the effect of direct interspecies electron transfer on syntrophic methanogenesis through thermodynamic analysis. (September 2019) - Gu, Mengqi; Yin, Qidong; Liu, Yu; Du, Jin; Wu, Guangxue
Abstract: Effects of redox materials, and types and concentrations of organic carbons on direct interspecies electron transfer (DIET) were thermodynamically analyzed. Redox materials with a low redox potential (below +0.033 V) and increasing substance concentrations could increase the reaction rate of DIET. The reaction rate of DIET reached 0.3390 h −1 with the addition of ferroferric oxide (Fe3 O4 ), which was much higher than that of acetoclastic and hydrogentrophic methanogenesis. Ethanol was the most favorable organic carbon in DIET, and the facilitation of DIET could be achieved with redox materials like c-type cytochromes and Fe3 O4 . Addition of redox materials with a negative redox potential and increasing initial organic carbon concentrations could promote DIET and improve the efficiency of methanogenesis. A mechanism of combined organic carbon and redox mediators affecting DIET was proposed. Furthermore, a new parameter, σ · η · cRM  / (γ · VSS + η · cRM ), representing electron transfer rate via DIET with the addition of redox mediators, was proposed for DIET modelling. Graphical abstract: Unlabelled Image Highlights: Redox materials with low redox potential could benefit the promotion of DIET. Redox materials and enriched microorganisms were key factors affecting DIET. Mechanism for organic carbon and redox mediator affecting DIET was proposed. The obtained thermodynamic parameters could be used for DIET modelling.